Trends in Vessel Atmospheric Emissions in the Central Mediterranean over the Last 10 Years and during the COVID-19 Outbreak - Martin Saliba; Francelle Azzopardi; Rebecca Muscat; Marvic Grima; Alexander Smyth; Jukka-Pekka Jalkanen; Lasse Johansson; Alan Deidun; Adam Gauci; Charles Galdies; Tonio Caruana; Raymond Ellul (Journal of Marine Science and Engineering, 2021)
Giordan Lighthouse, located on the island of Gozo in the Malta-Sicily Channel within the central Mediterranean region, is ideally located to study the primary sources of atmospheric pollution. A total of 10 years of data have been accumulated from the reactive gas and greenhouse gas detectors and the aerosol analyzers found at this Global Atmosphere Watch (GAW) regional station. The data has been evaluated, resulting in trends in emissions from shipping recorded within the same region coming to the fore. The other source of emissions that was evident within the recorded data originated from Mt. Etna, located on the island of Sicily and representing the highest active volcano in Europe. The aim of this paper is to investigate the effect of ship emissions on trace gases and aerosol background measurements at Giordan Lighthouse, including the putative influence of COVID-19 on the same emissions. The model used to evaluate ship emissions was the Ship Traffic Emission Assessment Model (STEAM). From trace gas measurements at Giordan Lighthouse, a slowly decreasing trend in sulfur oxide (SOx) and nitrogen oxide (NOx) emissions was noted. To better understand the air quality results obtained, the STEAM model was fed, as an input, an Automatic Identification System (AIS) dataset to describe the vessel activity in the area concerned. This study also investigates the effects of the COVID19 pandemic on marine traffic patterns within the area and any corresponding changes in the air quality. Such an analysis was carried out through the use of SENTINEL 5 data.